SATU LANGKAH, SATU DESA : TRANSFORMASI MENYELURUH BERBASIS INOVASI LOKAL DI PENITI LUAR - Agustin, Wirda; Hazdan, Muhammad Fahmi (LPPM Universitas Panca Bhakti, 2025)
Community service is a fundamental pillar of the Tridharma of Higher Education, which emphasizes the role of universities as catalysts for social, economic, and environmental development. One of its implementations is the Kuliah Kerja Nyata (KKN) program, designed to promote community empowerment based on local potential. Desa Peniti Luar, Kecamatan Jongkat, Kabupaten Mempawah, was chosen as the locus of activity due to its rich resources, particularly in the agricultural sector of rice and coconut plantations, which have not been optimally utilized. The fundamental problems faced by the community include low literacy, limited awareness of social issues (such as bullying and child protection), weak environmental management, and the need to strengthen food security and infrastructure development. The KKN activities were carried out through a participatory approach that integrates multidimensional programs. The education and social sectors were realized through literacy strengthening, social issue education, and the development of a village reading corner. The economic sector focused on empowering farmer groups by utilizing coconut waste and diversifying food through corn cultivation. The environmental sector was directed at waste awareness campaigns and strengthening clean living behaviors, while the physical development sector focused on creating a welcome monument and preparing a concrete road plan as a foundation for village infrastructure development. The results showed that KKN not only increased literacy capacity, social awareness, and environmental concern among the community but also strengthened the local economic base by utilizing village resources. Thus, KKN plays a strategic role as a means of social transformation and an accelerator of participatory, inclusive, and sustainable village development.